2020
DOI: 10.3390/genes11040378
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Genetic Diagnosis Yield in Inherited Retinal Dystrophies: Assigning Pathogenicity to Novel Non-canonical Splice Site Variants

Abstract: Aims: We aimed to validate the pathogenicity of genetic variants identified in inherited retinal dystrophy (IRD) patients, which were located in non-canonical splice sites (NCSS). Methods: After next generation sequencing (NGS) analysis (target gene panels or whole exome sequencing (WES)), NCSS variants were prioritized according to in silico predictions. In vivo and in vitro functional tests were used to validate their pathogenicity. Results: Four novel NCSS variants have been identified. They are located in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
1
13
1
Order By: Relevance
“…One of the current challenges in the genetic diagnosis of IRDs is the detection and functional validation of variants that have not been previously reported and whose functional significance remains unclear. New cis-acting mutations causing retina-specific splicing defects are usually tested in HEK293T cells using in vitro mini- and midi-genes splice assays because IRD genes are not commonly expressed in accessible human tissues [ 88 , 89 , 90 ]. However, HEK293T cells do not reproduce retinal cell conditions since they do not express retina-specific splicing factors and adjuvant proteins.…”
Section: The Role Of Alternative Splicing In Retinal Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…One of the current challenges in the genetic diagnosis of IRDs is the detection and functional validation of variants that have not been previously reported and whose functional significance remains unclear. New cis-acting mutations causing retina-specific splicing defects are usually tested in HEK293T cells using in vitro mini- and midi-genes splice assays because IRD genes are not commonly expressed in accessible human tissues [ 88 , 89 , 90 ]. However, HEK293T cells do not reproduce retinal cell conditions since they do not express retina-specific splicing factors and adjuvant proteins.…”
Section: The Role Of Alternative Splicing In Retinal Diseasementioning
confidence: 99%
“…Therefore, occasionally, they result in disease expression, particularly in those patients who carry only a pathogenic allele, thus explaining why some variants are found to be pathogenic in some individuals but not in others. Another example is the NCSS variant c.4849-8C>G, which has also been proved to be pathogenic since it lowers the value of the Pyrimidine tract upstream of the 3′ splice site of intron 34, thus producing transcripts with intron retention that leads to premature protein truncation ( Figure 4 B) [ 88 ].…”
Section: The Role Of Alternative Splicing In Retinal Diseasementioning
confidence: 99%
“…One alternative to circumvent these obstacles is to use in vitro minigenes, which directly determine whether single nucleotide polymorphisms (SNPs) disrupt splicing regulation. Many previous studies have validated the minigene assay as a viable approach to evaluate splicing alterations ( Spickett et al, 2016 ; Zernant et al, 2018 ; Bauwens et al, 2019 ; Toulis et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the multitude of loci associated with IRDs (almost 300 loci, ), molecular diagnostics often relies on targeted enrichment and high-throughput sequencing, either whole-exome (WES) [ 3 , 4 , 5 , 6 ] or gene panels [ 5 , 6 , 7 , 8 , 9 , 10 ]. Studies have reported that diagnostic yield when using these standard methods (WES/gene panels) is typically between 50% and 76%, depending, amongst other factors, on the specific clinical subtype being investigated [ 6 , 7 , 8 , 9 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%